2002
DOI: 10.1046/j.1442-2026.2002.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a tool to safely triage selected patients with chest pain to unmonitored beds

Abstract: Objective: To externally validate a chest pain protocol that triages low risk patients with chest pain to an unmonitored bed. Methods: Retrospective study of all patients admitted from the emergency department of a tertiary referral public teaching hospital with an admission diagnosis of ‘unstable angina’ or suspected ischemic chest pain. Data was collected on adverse outcomes and analysed on the basis of intention‐to‐treat according to the chest pain protocol. Results: There were no life‐threatening arrhythmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…In a sample of 244 patients who would have been assigned to an unmonitored bed, there were no deaths or life-threatening arrhythmias, four uncomplicated AMI and one acute pulmonary oedema within 72 h of admission. 10 There are also several studies that show low complication rates for patients admitted with suspected AMI who have a normal ECG. [11][12][13] Taken together with the current study, there is now strong evidence that a subgroup of patients with suspected ACS who require hospital admission can, on the basis of clinical and biochemical features in the ED, be safely assigned to unmonitored beds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a sample of 244 patients who would have been assigned to an unmonitored bed, there were no deaths or life-threatening arrhythmias, four uncomplicated AMI and one acute pulmonary oedema within 72 h of admission. 10 There are also several studies that show low complication rates for patients admitted with suspected AMI who have a normal ECG. [11][12][13] Taken together with the current study, there is now strong evidence that a subgroup of patients with suspected ACS who require hospital admission can, on the basis of clinical and biochemical features in the ED, be safely assigned to unmonitored beds.…”
Section: Discussionmentioning
confidence: 99%
“…have conducted an external validation of the WHCPP. In a sample of 244 patients who would have been assigned to an unmonitored bed, there were no deaths or life‐threatening arrhythmias, four uncomplicated AMI and one acute pulmonary oedema within 72 h of admission 10 . There are also several studies that show low complication rates for patients admitted with suspected AMI who have a normal ECG 11−13 .…”
Section: Discussionmentioning
confidence: 99%
“…1,3 The ED population presenting with chest pain represent a very different risk category, as a diagnosis of ACS is only established in 12-15%, 4 and arrhythmias are rare, occurring in 0-2% of all patients evaluated for chest pain. [4][5][6][7] The incidence among patients without ECG evidence of acute ischaemia or infarction would be expected to be even lower. A prospective observational study of ED chest pain patients with normal or non-specific ECGs who were placed on continuous monitoring demonstrated only 0.2% of monitor alarms were associated with an arrhythmia requiring intervention, representing one 4 The literature has shown that certain ED patients can be safely removed from continuous cardiac monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing amount of evidence to suggest that CP patients at low‐to‐intermediate risk of developing a life‐threatening complication can be safely managed after hospital admission without continuous cardiac monitoring after an initial observation period in the ED 3–7 . Generally, these patients are stable, with no ongoing CP or cardiac rhythm disturbances, and have non‐ischaemic electrocardiograms (ECG) and normal cardiac markers during their ED stay.…”
Section: Introductionmentioning
confidence: 99%